The Motivation of the Tenth Grade Students in Learning English at SMKN 1 Tana Toraja - Linerda Tulak Tondok (Publikasi dan UKI Press UKI Toraja., 2019)
The objective of this research is to find out the motivation in learning English by tenth grade students at SMK N 1 Tana Toraja. To achieve the objective of the study, the writer conducted quantitative descriptive method. The participant of the research was tenth grade students of SMK N 1 Tana Toraja academic year 2017/2018. This research employed a random sampling technique. The data was obtained from questionnaire was to find out the motivation of the tenth grade students in learning English at SMK N 1 Tana Toraja. The result of this research showed that the data analysis through questionnaire was used to find out the motivation in learning English of tenth grade students at SMK N 1 Tana Toraja. Based on the result of the questionnaire, the writer found that were four intrinsic motivation in learning English such us; important, interest, increase our knowledge and self-confidence, challenge and four extrinsic motivation in learning English such us; parents or the other people, get reward, place, have many friends from another countries. The students more chose intrinsic motivation.